Mobile computing, applications, and services : 7th International Conference, MobiCASE 2015, Berlin, Germany, November 12-13 2015 ; revised selected papers /: 7th International Conference, MobiCASE 2015, Berlin, Germany, November 12-13 2015 ; revised selected papers. ([2015]) - Unknown
No abstract available